2016
DOI: 10.1108/ijqrm-11-2014-0184
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis and life cycle cost optimization: a case study from Indian industry

Abstract: Purpose – Reliability analysis is required to identify the components or subsystems with low reliability for a given designed performance. Life cycle cost analysis helps understand the cost implications over the entire life span of a product. The purpose of this paper is to present a case study describing reliability analysis and life cycle cost optimization of a band saw cutting machine manufactured and used in India. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 17 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Yang et al [50], using field data of machining centers, showed the shape parameter to be 1.17 for the electrical system, 1.77 for the CNC system, and 2 for the servo system (implying that their hazard rates were increasing throughout the life). The studies by Waghmode and Patil [51], Patil et al [52], Keller et al [53], and Dai et al [54] on computerized numerical control machine tools show that the hazard rates of their electronic components are not constant. Figure 4 shows the hazard rate curve of the electronic system of a CNC machine tool.…”
Section: B Useful Life Periodmentioning
confidence: 99%
“…Yang et al [50], using field data of machining centers, showed the shape parameter to be 1.17 for the electrical system, 1.77 for the CNC system, and 2 for the servo system (implying that their hazard rates were increasing throughout the life). The studies by Waghmode and Patil [51], Patil et al [52], Keller et al [53], and Dai et al [54] on computerized numerical control machine tools show that the hazard rates of their electronic components are not constant. Figure 4 shows the hazard rate curve of the electronic system of a CNC machine tool.…”
Section: B Useful Life Periodmentioning
confidence: 99%
“…Reliability and maintainability analysis facilitates in improving competitiveness and customer satisfaction (Madu, 2005). Waghmode and Patil (2016) performed reliability analysis to optimize the life cycle cost. Kumar et al (2017) performed the availability and cost analysis of an engineering system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reliability is the characteristic of a system expressed by the probability that a system/component can perform a required function for which it was designed, in given conditions for a given period of time (Waghmode & Patil, 2016). Mathematical definition of reliability is presented by…”
Section: Reliabilitymentioning
confidence: 99%